Penegakan Hukum dalam Penanggulangan Kejahatan Pertambahan Pasir Ilegal - Syahnas Mauthia Setia Putri; Rinaldi Amrullah; Emilia Susanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The crime of illegal sand mining is a problem that requires the attention of various parties. The current phenomenon is that illegal mining is rampant among individuals and companies. Based on data from the Central Lampung Police, illegal mining crimes occur every year, while data from Walhi Lampung and the Environmental Service shows that there are still very few mining activities that have IUPs. This shows that illegal mining crime is a problem that must be handled by various elements. The research method used is a Normative Juridical and Empirical Juridical approach. Sources and types of data in research were obtained from field studies with interviews and literature studies. This research was conducted at the Central Lampung Police, lecturers at the Faculty of Law, Unila University, Walhi Lampung, and the Environmental Service. The results of this research describe that the police do not only focus on law enforcement, but also focus on preventative efforts to tackle illegal mining crimes. Even though Law Number 3 of 2020 concerning Mineral and Coal Mining, the Police does not contain the authority of the Police in mining crimes. However, the police as the front guard of law enforcement officials must make countermeasures. This includes pre-emptive efforts to identify potential risks that cause illegal mining to occur. Monitoring efforts are carried out actively and periodically and are routinely used as an effort to detect potential crimes before they develop into real crimes. The preventive approach involves outreach and education activities in areas where there is potential for mining to increase public awareness about the negative impacts of illegal mining crimes. Then the last one is repressive efforts as a form of providing legal certainty